Universals and particulars. The case of liberal cultural nationalism : review article - Seglow, Jonathan (1998)
Comenta la obra de tres autores: Will Kymlicka "Multicultural citizenship". David Miller "On nationality" y Charles Taylor "The politics of recognition"
Keywords: Kymlicka, Will; Miller, David; Taylor, Charles; Liberalismo; Nacionalismo; Grupo sociocultural; Ciudadano; Identidad cultural